Determining nursing students’ evidence-based practice competencies and the effective factors - Aslan, Hakime; Pekince, Hatice (My University, 2019)
This research was carried out to determine the evidence-based practice (EBP) competencies of nursing students studying in a university and the effective factors. This study is descriptive and cross-sectional of nursing students studying at Inonu University. In the research, a sample selection was not made, as the research aimed to reach the whole university. In the study, two data collection tools were used. A personal information form was developed by the researcher to determine the socio-demographic and academic achievement status of the students, as was a student evidence-based practice questionnaire (S-EBPQ). The data were collected from 15 September to 1 October 2018 by face-to-face interview technique. The mean score of the students in the S-EBPQ was found to be 83.75±10.02; the mean score obtained from the behavior subscale was found to be 48.87±7.54; the mean score obtained from the skill subscale was 19.70±3.67, and the mean score obtained from the knowledge subscale was 18.63±3.29. As a result of this study evaluating the EBP competencies of nursing students, the students’ knowledge, skills, and attitudes subscale, as well as their total average score, were found to be above average.
Keywords: Hemşirelik